Liquid chromatography tandem mass spectrometry identification of apple polyphenol metabolites in human urine and plasma - Gallant, Vicki Ann (2010)
Apples are a major dietary source of polyphenols in the Western diet and contain procyanidins, hydroxycinnamic acids, flavanols, dihydrochalcones and flavonols. Despite their abundance and familiarity very little research into their metabolism has been performed; research is required to elucidate the metabolic products of these polyphenols and characterise their absorption and excretion pathways. A human intervention study was designed specifically to investigate the absorption, metabolism, excretion and biokinetcs of apple polyphenols. Male volunteers (n = 9) consumed a supermarket apple juice substituted with water as the control phase, and the same apple juice substituted with a high polyphenol cider apple extract as the test phase. Blood samples were taken over 0-24 h and urine samples were collected at 0-4 h, 4-8 h and 8-24 h. A rapid, validated and novel single LC/ES/IMS/MS method was developed and validated for the analysis of a wide range of polyphenols and their metabolites in these urine and plasma samples (after sample preparation). Apple polyphenolrelated metabolites were identified using LC/MS/MS and MS2; nine urinary metabolites and seven plasma metabolites were identified, mostly for the first time after apple consumption. Data on the excretion, bioavailability and biokinetics of these metabolites, including products of the colonic micro flora, were obtained. In urine, the major apple-related polyphenolic metabolites identified were dihydroxyphenyl valerolactone sulfate and 5- (3', 4'- dihydroxyphenyl) -y- valerolactone glucuronide; both colonic bacterial metabolites which appear at their maximum concentrations 4-8 h post apple ingestion. Minor metabolites included (-) epicatechin sulfate and glucuronide conjugates. In plasma, 3, 4-dihydroxyphenylacetic acid, 5- (3',4'-dihydroxyphenyl) -y- valerolactone glucuronide and dihydroxyphenyl valero lactone sulfate predominate; Tmax values of 5-6 h were observed. Minor plasma metabolites included phloretin (Cmax291 ± 175 nM) and p-coumaric acid (Cmax 634 ± 225 nM). In conclusion, the project has identified apple-related polyphenol metabolites in human urine and plasma; many for the first time after apple consumption. Important biokinetic parameters have also been reported for these metabolites.